Evaluasi Pembelajaran dalam Meningkatan Mutu Pendidikan di Sekolah Dasar - Septiani, Astrid Nur; Pratiwi, Desti; Rossy, Rossy (MASALIQ, 2023)
Learning evaluation is a process that involves measuring the achievement of learning goals, providing feedback for learning improvement, identifying individual student needs, enhancing teaching quality, and assessing and holding the education system accountable. This article also highlights several challenges that need to be addressed in learning evaluation in elementary schools, such as an overly cognitive-focused approach, excessive pressure on students, and teachers’ qualifications to conduct effective evaluations. A literature review is used as the method in this article, collecting and analyzing various relevant literature sources. The article concludes that learning evaluation that is oriented towards comprehensive student development, considers both cognitive and non-cognitive aspects, and involves well-trained teachers can provide valuable information for enhancing learning and achieving better education quality in elementary schools.